2020
DOI: 10.1016/j.stemcr.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-Associated Metabolomic Phenotype in Primary and iPSC-Derived Mesenchymal Stromal Cells

Abstract: Long-term culture of primary cells is characterized by functional and secretory changes, which ultimately result in replicative senescence. It is largely unclear how the metabolome of cells changes during replicative senescence and if such changes are consistent across different cell types. We have directly compared culture expansion of primary mesenchymal stromal cells (MSCs) and induced pluripotent stem cell-derived MSCs (iMSCs) until they reached growth arrest. Both cell types acquired similar changes in mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…However, during culture expansion, iMSCs undergo replicative senescence-like primary MSCs. Accordingly, we have recently demonstrated that MSCs and iMSCs entered a senescent state after 21.3 ± 1.4 and 17.1 ± 3.8 cumulative population doublings, respectively [45]. Furthermore, this process is associated with very similar changes in morphology, differentiation potential, expression of senescence-associated betagalactosidase, transcriptome, epigenome, and metabolome [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, during culture expansion, iMSCs undergo replicative senescence-like primary MSCs. Accordingly, we have recently demonstrated that MSCs and iMSCs entered a senescent state after 21.3 ± 1.4 and 17.1 ± 3.8 cumulative population doublings, respectively [45]. Furthermore, this process is associated with very similar changes in morphology, differentiation potential, expression of senescence-associated betagalactosidase, transcriptome, epigenome, and metabolome [45].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, senescent MSCs did not appear to utilise anaerobic glycolysis and instead, produced ATP primarily via oxidative phosphorylation, a metabolic activity more consistent with differentiated cells [37]. However, a more recent study has shown that senescenceassociated changes in MSCs included down-regulation of nicotinamide ribonucleotide and up-regulation of orotic acid, and reflected the metabolic switch from oxidative to glycolytic pathways, possibly to avoid further damage by ROS [38].…”
Section: Replicative and Stress-induced Senescence In Msc Cultures: Mmentioning
confidence: 99%
“…Contradictory results have been published concerning senescent MSC metabolism; Capasso et al [39] documented a shift from glycolysis to oxidative phosphorylation, whereas Fernandez-Rebollo et al [160] observed a metabolic switch from oxidative to glycolytic pathways, possibly to avoid further damage by ROS.…”
Section: Ros (Reactive Oxygen Species) Production: In Vitro Datamentioning
confidence: 99%